Namjera, ciljevi, zadaci, organizacija, mjesto i uloga jedinstvene vojske SRJ / Intention, Objectives, Organization, Tasks and the Role of Consolidated: Vojske jugoslavije/„Vojske Republike Srpske”/„Srpske vojske krajine”, de iure i de facto organa države Savezne republike jugoslavije, u (iz)vršenju genocida u Republici Bosni - (nastavak) / Fry - Rump Yugoslavia Army / "The Republic of Srpska Army" / "republic of Serbian Krajina Army", De iure and De facto of Federal Republic of Yugoslavia State Organ, in Genocide in the Republic of Bosnia and Herzegovina - (Continued) - Čekić, Smail (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Near the end of the 20th century, Serbia and Montenegro / the Rump Yugoslavia conducted an invasive, aggressive war against the Republic of Bosnia and Herzegovina and Republic of Croatia¸, committed numerous forms of crimes against humanity and international law, including the genocide against Bosniaks, members of the national, ethnic and religious groups such. In that war, Serbia and Montenegro/the Rump Yugoslavia played a key role, especially its armed forces (YPA/YA/ ―Republika Srpska Army‖/‖Serbian Krajina Army―, special units of the Ministry of Internal Affairs of the Republic of Serbia and other armed units). Starting from the above facts, this article deals with the extremely complex, scientific and social problem.